(untitled) (Journal of Health, Population and Nutrition, 2009)
Bangladesh is currently one of the very few countries in the world, which is on target for achieving the Millennium Development Goal (MDG) 4 relating to child mortality. There have been very rapid reductions in mortality, especially in recent years and among children aged over one month. However, this rate of reduction may be difficult to sustain and may impede the achievement of MDG 4. Neonatal deaths now contribute substantially (57%) to overall mortality of children aged less than five years, and reductions in neonatal mortality are difficult to achieve and have been slow in Bangladesh. There are some interesting attributes of the mortality decline in Bangladesh. Mortality has declined faster among girls than among boys, but the poorest have not benefited from the reduction in mortality. There has also been a relative absence of a decline in mortality in urban areas. The age and cause of death pattern of under-five mortality indicate certain interventions that need to be scaled up rapidly and reach high coverage to achieve MDG 4 in Bangladesh. These include skilled attendance at delivery, postnatal care for the newborn, appropriate feeding of the young infant and child, and prevention and management of childhood infections. The latÂest (2007) Bangladesh Demographic and Health Survey shows that Bangladesh has made sustained and remarkable progress in many areas of child health. More than 80% of children are receiving all vaccines. The use of oral rehydration solution for diarrhoea is high, and the coverage of vitamin A among children aged 9-59 months has been consistently increasing. However, poor quality of care, misperceptions regarding the need for care, and other social barriers contribute to low levels of care-seeking for illnesses of the newborns and children. Improvements in the health system are essential for removing these barriers, as are effective strategies to reach families and communities with targeted messages and information. Finally, there are substantial health-system challenges relating to the design and implementation, at scale, of interventions to reduce neonatal mortality. Key words: Child health; Child mortality; Infant health; Infant mortality; Bangladesh doi:10.3329/jhpn.v26i3.1895 J Health Popul Nutr 2008 Sept:26(3):273-279